GRADUATE SCHOOLS OF BUSINESS. - Newlove, G. H. (The Accounting Review, 1926)
The tenth annual meeting of the American Association of University Instructors in Accounting was especially noteworthy because of the able papers given on the subject "Research Work in Universities." Inspired by these papers the present writer decided to ascertain approximately what graduate work in applied economics the American universities were doing. As there were no data available on this subject, a survey was started. This paper is the result of the survey conducted by the Association. The basic courses in commercial law are so fundamental that practically all graduate schools of business offer them. The commercial law courses are 8.4% of the total applied economic courses in non-urban schools and 6.2% in urban schools. This variation is due to the difference in the total number of courses offered in non-urban and urban schools as the number of commercial law courses offered is practically constant. The unusual number of commercial law courses offered at American University and Pennsylvania University is doubtless due to local conditions, the excellent standing of the graduate law school at the former and unusual complexities of the State law code at the latter. Business management ranks first or is tied for first among the applied economic groups in five out of the twenty-seven schools.